MINDFULNESS INNOVATION APPROACH TO DEVELOPING HAPPINESS INDICATORS FOR PERSONNEL AT INTERNATIONAL BUDDHIST STUDIES COLLEGE - Neminda, Neminda; Tuan, Nguyen Anh; Tshering, Ugyen; Ampan, Nadapat; Mahatthanadull, Sanu; Vicitta, Vicitta (Jurnal Agama Buddha dan Ilmu Pengetahuan, 2025)
This study examines a Mindfulness Innovation framework for developing happiness indicators among personnel at the International Buddhist Studies College (IBSC). Grounded in Theravāda, Mahāyāna, and Vajrayāna (TMV) Buddhist traditions, it addresses the need for work-life balance and well-being strategies in an international academic setting. The objectives were to identify mindfulness-based happiness indicators for IBSC personnel, evaluate the impact of mindfulness innovations on stress reduction and happiness within TMV frameworks, and assess the overall effectiveness of this innovation approach in developing happiness indicators. A mixed-methods design was used, combining qualitative interviews with 10 key informants from Thailand, Bhutan, Vietnam, Korea, and Hungary and a quantitative pilot intervention. Tools included structured questionnaires, interview guides, and observational checklists. Pre- and post-intervention measures of emotional resilience, job satisfaction, and life satisfaction were analyzed via paired-samples t-tests. The 5-day mindfulness intervention drew on TMV practices; an example pilot course significantly increased participants’ self-reported happiness (mean score 4.08 to 4.26, p<.01). Thematic analysis of interviews identified core happiness dimensions that were both culturally-specific and universal across traditions. The findings empirically support a culturally sensitive model of mindfulness-based well-being: TMV-inspired practices improved well-being in a diverse academic community, producing validated happiness indicators tailored to the IBSC context. This contributes to Buddhist and organizational psychology by linking traditional Buddhist wisdom with employee happiness science, offering an evidence-based model to foster a balanced, supportive academic environment.